BURUNG WALET DALAM KARYA SENI GRAFIS - Anda Rizka Damanik; Ariusmedi Ariusmedi (Serupa The Journal of Art Education, 2021)
The making of the final work of graphic art using serigraphy techniques is to visualize the uniqueness of the swallow, including its characters and anatomy. Several stages were taken in carrying out this final work including preparation, elaboration, synthesis, concept realization and completion stages. By carrying out these stages, ten graphic art works visualizing the various uniqueness of the swallow birds, including the titles "Tersesat", "Straight", Doubt "," Group ".Kata Kunci: Burung Walet, Keunikan, Seni Grafis.